Vungu Téla Estudo da Música Santomense: Uma proposta de métodos, técnicas e objetivos - Magdalena Bialoborska (Cadernos de Estudos Africanos)
The music of Sao Tome and Principe, small archipelago located about 300 km off the west coast of Africa, which is considered to be a Creole society, is relatively little known. The musical circuit, both past and present, is limited to the inhabitants of the islands and Santomean diaspora. There is a significant lack of sources that focus on the various musical genres and also on the music that is part of rituals, theatre and festivities. Additionaly, the interpretation of most of the genres from the islands is becoming less frequent. This article comes as a proposal for a broad study of the Santomean music and it aims to present possible methods, techniques of collecting the dates and the ways of analysing the musical material, as well as the definition of the steps and the objectives of this research. It also presents a possible classification of the Santomean music.